The need for post-operative vasopressor infusions after major gynae-oncologic surgery within an ERAS (Enhanced Recovery After Surgery) pathway - Michèle Bossy; Molly Nyman; Thumuluru Kavitha Madhuri; Anil Tailor; Jayanta Chatterjee; Simon Butler-Manuel; Patricia Ellis; Aarne Feldheiser; Ben Creagh-Brown (Perioperative Medicine, 2020)
Abstract Background Hypotension following major abdominal surgery is common, and once hypovolaemia has been optimally treated, is often due to vasodilation which can be treated with vasopressor infusions. There is unpredictability in the dose and duration of post-operative vasopressor infusions, and factors associated with this have not been determined. Methods We present a case series of consecutive patients who received major gynae-oncology surgery delivered within an Enhanced Recovery After Surgery (ERAS) pathway at a single institution. Patients were electively admitted from theatre directly to the intensive care unit (ICU). Data was collected prospectively into electronic databases (Philips ICCA, Wardwatcher) and then retrospectively collated and appropriate statistical analyses were performed. In the absence of a consensus definition of vasoplegia, we, necessarily arbitrarily, chose a noradrenaline dose of > 0.1 mcg/kg/min at 08:00 on the first post-operative day. The rationale is that this would be more than would typically be expected to counteract the vasodilatory effects of epidural analgesia, which is commonly used at our institution. Results Data was collected from 324 patients, all treated between February 2014 and July 2016. The average age was 67 years and 39% received neoadjuvant chemotherapy. The commonest tumour type was ovarian (58%). The median estimated blood loss was 800 ml and epidural analgesia was used in 71%. Fifty per cent received post-operative vasopressor infusions: factors associated with this included epidural use and estimated blood loss. Nineteen per cent met our criteria for vasoplegia: factors associated with this included CRP on post-operative day 1 and P-POSSUM morbidity score. Hospital and ICU length of stay was prolonged in those who had vasoplegia. Conclusions Patients commonly receive vasopressors following major gynae-oncologic surgery, and this can be at relatively high doses. Clinical factors only accounted for a minority of the variability in vasopressor usage—suggesting considerable biological variability. Optimal care of patients having major abdomino-pelvic surgery may include advanced haemodynamic monitoring and ready availability of infused vasopressors, in a suitable environment.